1984
DOI: 10.1677/joe.0.1020305
|View full text |Cite
|
Sign up to set email alerts
|

Increase in ovulation rate after active immunization of sheep with inhibin partially purified from bovine follicular fluid

Abstract: Four Romney ewes were actively immunized with a partially purified preparation of inhibin derived from bovine follicular fluid and their ovulation rates in four successive oestrous cycles were compared with those of four ewes receiving adjuvant alone. The ovulation rates of the ewes immunized with the inhibin preparation were significantly higher than those of the control ewes (2.06 +/- 0.16 (S.E.M.) vs 1.31 +/- 0.06 ovulations/ewe, n = 4). Plasma concentrations of FSH and LH, measured in blood samples taken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
1

Year Published

1986
1986
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 13 publications
3
21
1
1
Order By: Relevance
“…This study confirms and extends previous reports that active immunization of sheep against inhibin-containing preparations including partially purified bovine follicular fluid (Henderson et al, 1984;O'Shea et al, 1984;Cummins et al, 1986), recombinant DNA-derived inhibin subunits (Forage et al, 1987;Tsonis et al, 1989;Mizumachi et al, 1990) and chemically synthesized frag¬ ments of inhibin (Wrathall et al, 1990) can promote substantial (2^1-fold) increases in ovulation rate. It was demonstrated that the plasma of ewes immunized against a synthetic fragment of the asubunit of inhibin contained antibodies that bound 125I-labelled native bovine inhibin (MT 32 000), such antibodies being absent in nonimmunized and carrier-protein-immunized control ewes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study confirms and extends previous reports that active immunization of sheep against inhibin-containing preparations including partially purified bovine follicular fluid (Henderson et al, 1984;O'Shea et al, 1984;Cummins et al, 1986), recombinant DNA-derived inhibin subunits (Forage et al, 1987;Tsonis et al, 1989;Mizumachi et al, 1990) and chemically synthesized frag¬ ments of inhibin (Wrathall et al, 1990) can promote substantial (2^1-fold) increases in ovulation rate. It was demonstrated that the plasma of ewes immunized against a synthetic fragment of the asubunit of inhibin contained antibodies that bound 125I-labelled native bovine inhibin (MT 32 000), such antibodies being absent in nonimmunized and carrier-protein-immunized control ewes.…”
Section: Discussionsupporting
confidence: 90%
“…As in this earlier study, no correlation was found between inhibin antibody titre and ovulation rate of individual ewes, an observation which is consistent with the report of Forage et al (1987) but contradicts the recent findings of Tsonis et al (1989). In view of the conflicting evidence about whether active immunization against inhibin actually raises FSH secretion (Henderson et al, 1984;O'Shea et ai, 1984;Cummins et ai, 1986;Al-Obaidi et al, 1987;Findlay et al, 1989;Wrathall et al, 1990), it is still not possible to state unequivocally that the increased ovulation rate observed in inhibin-immunized ewes is due to a rise in plasma FSH levels, which would be a predicted consequence of inhibin immunoneutralization. The present study, however, provides further evidence to support this explanation since plasma FSH levels were significantly higher (25%) than in control ewes after the second booster immunization, whereas plasma LH levels did not differ significantly between immunized and control ewes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active immunization against INH neutralizes endogenous INH and increases the ovulation rate in mammals [6,7,10,[37][38][39]. The results of the present study showed no significant difference in egg production between birds that were actively immunized against INH and control hens, even though immunization significantly increased the number of preovulatory yellow follicles and significantly increased FSH␤ subunit mRNA content in the anterior pituitary.…”
Section: Discussioncontrasting
confidence: 42%
“…This may be explained by the paracrine effect of INH on follicular maturation, as direct injection of rhINH A into immature rat ovaries enhances follicle maturation, which is indicated by follicular size [40]. It still remains to be proven that the ovarian response to rtINH␣ immunization is precipitated by a rise in FSH secretion (no FSH assay is available that measures circulating turkey FSH), because several studies have found plasma FSH to be unaffected by immunization despite an increased ovulation rate [9,37,39]. Immunization of hens in their first reproductive cycle with rtINH␣ increased (7.6-fold) FSH␤ subunit mRNA content more than it did in second-reproductive-cycle hens (twofold).…”
Section: Discussionmentioning
confidence: 99%